2007
DOI: 10.1063/1.2424700
|View full text |Cite
|
Sign up to set email alerts
|

Simulated scaling method for localized enhanced sampling and simultaneous “alchemical” free energy simulations: A general method for molecular mechanical, quantum mechanical, and quantum mechanical/molecular mechanical simulations

Abstract: A potential scaling version of simulated tempering is presented to efficiently sample configuration space in a localized region. The present "simulated scaling" method is developed with a Wang-Landau type of updating scheme in order to quickly flatten the distributions in the scaling parameter lambdam space. This proposal is meaningful for a broad range of biophysical problems, in which localized sampling is required. Besides its superior capability and robustness in localized conformational sampling, this sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 56 publications
1
106
0
1
Order By: Relevance
“…Tempering is a technique (12,(41)(42)(43)(44)(45)(46)(47)(48) that accelerates sampling by occasionally raising and lowering the temperature. In this study, we adopted a single-trajectory-based tempering method reported previously (12) for computing efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Tempering is a technique (12,(41)(42)(43)(44)(45)(46)(47)(48) that accelerates sampling by occasionally raising and lowering the temperature. In this study, we adopted a single-trajectory-based tempering method reported previously (12) for computing efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…With the MRWQ scheme, one might expect even better sampling since walking between λ windows might induce "conformational tunneling" effect [67]. However, we observe that MRWQ simulations lead to too low a pK a shift by more than 1 pK a unit.…”
Section: Pk a Calculations For Buried Residuesmentioning
confidence: 90%
“…The need of employing enhanced sampling techniques in the free energy simulations, [39,40] on the other hand, seems much more compelling and can potentially make a very large impact on the computed pK a values. Multiple nanoseconds of simulations per λ window in the most straightforward thermodynamic integration framework, as done here, are sufficient only if the structural response is very local in nature and the involvement of multiple hydration states [11] is not severe.…”
Section: Discussionmentioning
confidence: 99%